e-Custormer Relationship Management and Service Quality as Intervening Trust variables, Brand Image and Behavioral Control on Student Satisfaction in the Accounting S1 Study Program : (Case Study on Accounting S1 Study Program Students at Private Universities in Lamongan Regency) - Darianto, Darianto; Nugroho, Mulyanto; Halik, Abdul (Technium Business and Management, 2022)
This study aims to examine and analyze the effect of e-Customer Relationship Management as anvariable Intervening Trust, Brand Image, Behavioral Control on Student Satisfaction (a case study on students of the Accounting S1 Study Program at PTS Lamongan Regency. The sample used in this study was 306 using a questionnaire to collect data. The sampling technique used Proportional Rondom Sampling. In this study The estimation used is generalized Least Square Estimation, which is the subject available to researchers when data collection is carried out. Data analysis techniques using SmartPLS - SEM analysis produce validity, reliability tests, classical assumption tests using Multicollinearity tests and hypothesis testing. The results of this study indicate that thevariable Trust has a positive and significant effect on e-CRM and student satisfaction, but has a negative and insignificant effect on service quality, the brand image variable has a positive and significant effect on e-CRM and service quality, and has a positive and significant effect on t on student satisfaction, behavioral control variables have a positive and significant effect on e-CRM, and can mediate non-positively and insignificantly on e-CRM and student satisfaction, and mediate positively and significantly between service quality.